(x+2)(x-3) - (2x-5)(x+3)= x(x-5)

0 голосов
68 просмотров

(x+2)(x-3) - (2x-5)(x+3)= x(x-5)


Алгебра (754 баллов) | 68 просмотров
0

ответ - 2 числа?

Дан 1 ответ
0 голосов
Правильный ответ
(x+2)(x-3)-(2x-5)(x+3)=x(x-5)
x^2-3x+2x-6-(2x^2+6x-5x-15)=x^2-5x
-2x^2+3x+9=0
2x^2-3x-9=0
D=b^2-4ac
D=(-3)^2-4*2*(-9)=9+72=81D\ \textgreater \ 0⇒2 р.д.к.
x_1= \frac{-b+ \sqrt{D} }{2a}
x_2= \frac{-b- \sqrt{D} }{2a}
x_1= \frac{3+ \sqrt{81} }{2*2} = \frac{12}{4} =3
x_2= \frac{3- \sqrt{81} }{4} = \frac{3-9}{4} = -\frac{6}{4} =-1.5
Ответ: -1.5;3
(18.3k баллов)